Sequence Variation in the Outer Membrane Protein-Encoding Gene cmeC, Conferring Multidrug Resistance among Campylobacter jejuni and Campylobacter coli Strains Isolated from Different Hosts - Fakhr, Mohamed K. (American Society for Microbiology, 2007)
A novel PCR primer pair was used to detect the presence of cmeC in 131 Campylobacter jejuni and C. coli strains isolated from various hosts (cattle, turkeys, humans, and pigs). DNA sequence analysis revealed a high degree of genetic variation between the two species, while extremely limited genetic variation among isolates of the same species was detected.